Analisis Pola Asuh Permisif dalam Perkembangan Sosial Emosional Anak Era Digital di Kober Al-Amin - Ila Mustakimah; Imas Masitoh (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2025)
This study aims to analyze permissive parenting in the social emotional development of children in the digital era at Kober Al-Amin. This research uses a qualitative approach with phenomenological method. Data collection techniques were conducted through interviews, observations, complete open and directed discussions, and documentation studies. The results showed that there are two impacts of permissive parenting. The positive impact of this parenting is that children are independent, have good creativity, have a high level of imagination because there is no benchmark from parents or educators and then poured into their lives. While the negative impact in permissive parenting that we found is that if parents do not supervise children, it is feared that children will behave badly because of lack of parental supervision.